Environmentally Sustainable Functionalized WS2 Nanoparticles as Curing Promoters and Interface Modifiers in Epoxy Nanocomposites - Lyazzat Tastanova; Amirbek Bekeshev; Sultan Nurlybay; Andrey Shcherbakov; Anton Mostovoy (Nanomaterials)
This study investigates the effect of the surface functionalization of tungsten disulfide (WS2) nanoparticles with aminoacetic acid (glycine) on the structure, curing behavior, and mechanical performance of epoxy nanocomposites. Aminoacetic acid, as a non-toxic, bio-based modifier, enables a sustainable approach to producing more efficient nanofillers. Functionalization, as confirmed by FTIR, EDS, and XRD analyses, led to elevated surface polarity and greater chemical affinity between WS2 and the epoxy matrix, thereby promoting uniform nanoparticle dispersion. The strengthened interfacial bonding resulted in a notable decrease in the curing onset temperature—from 51 °C (for pristine WS2) to 43 °C—accompanied by an increase in polymerization enthalpy from 566 J/g to 639 J/g, which reflects more extensive crosslinking. The SEM examination of fracture surfaces revealed tortuous crack paths and localized plastic deformation zones, indicating superior fracture resistance. Mechanical testing showed marked improvements in flexural and tensile strength, modulus, and impact toughness at the optimal WS2 loading of 0.5 phr and a 7.5 wt% aminoacetic acid concentration. The surface-modified WS2 nanoparticles, which perform dual functions, not only reinforce interfacial adhesion and structural uniformity but also accelerate the curing process through chemical interaction with epoxy groups. These findings support the development of high-performance, environmentally sustainable epoxy nanocomposites utilizing amino acid-modified 2D nanofillers.